Asymmetric SN2′-type C–H functionalization of arenes with propargylic alcohols. Issue 10 (4th September 2017) - Wu, Shangze; Huang, Xin; Fu, Chunling; Ma, Shengming
Abstract : The first example of transition metal-catalyzed stereo-defined syn -β-OH elimination! A [Cp*RhCl2 ]2 -catalyzed allenylation reaction of available arenes with propargylic alcohols afforded fully substituted allenes with excellent ees. Abstract : Herein we present the first example of transition metal-mediated stereodefined β-OH elimination, an atom economical [Cp*RhCl2 ]2 -catalyzed SN 2′-type coupling between easily available arenes and non-terminal tertiary 2-alkynylic alcohols at rt affording fully substituted allenes with H2 O as the only by-product. When optically active propargylic alcohols were used, asymmetric allenylation was realized with perfect chirality transfer. It is unveiled that the reversed regioselectivity for the C–C triple bond insertion is induced by the steric effect of the tertiary carbon center as well as the weak coordination nature of the hydroxyl oxygen with Rh, which is also responsible for the stereospecificity of the rather uncommon β-OH elimination forming allenes.